REVIEW OF SOCIOECONOMIC DISPARITIES: THE INFLUENCE OF SOCIOECONOMIC STATUS ON ACCESS TO QUALITY EDUCATION IN URBAN AND RURAL KASHMIR, INDIA - Zubaida Ahad (CV. Radja Publika, 2025)
The influence of socioeconomic status (SES) on access to quality education has long been a topic of significant concern, particularly in regions where disparities between urban and rural areas are pronounced. This study explores the impact of SES on educational access in the Kashmir region, focusing on the contrasting realities faced by urban and rural populations. In particular, it seeks to understand how factors such as parental education, household income, infrastructure availability, digital access, and gender influence educational outcomes in these areas. The research was conducted through a combination of quantitative and qualitative methods, including surveys, government reports, and focus group discussions involving parents, teachers, and students from both urban (Srinagar, Anantnag) and rural (Kupwara, Pulwama, Bandipora) regions. The findings reveal significant disparities between urban and rural areas, with urban households generally experiencing higher socioeconomic status, better infrastructure, and greater access to educational resources. Urban students benefit from better parental involvement, higher educational investment, and access to modern facilities, including libraries, science labs, and digital tools. Conversely, rural households, particularly those with lower income and education levels, face substantial barriers to accessing quality education. In rural areas, educational facilities are often under-resourced, with overcrowded classrooms, inadequate teaching materials, and limited access to digital platforms. The digital divide further exacerbates these inequalities, as urban students are better equipped to engage with e-learning platforms, while rural students struggle with limited access to technology and internet connectivity. Moreover, gender disparities are pronounced in rural Kashmir, where cultural norms often hinder female educational participation. Female students face additional challenges, such as a lack of sanitation facilities and safety concerns, which contribute to higher dropout rates. The impact of the ongoing conflict in Kashmir further complicates these issues, disrupting the academic calendar and contributing to teacher absenteeism and a lack of stability in rural areas. This study underscores the need for targeted policy interventions to address these inequities, including infrastructure development, digital inclusion, gender-sensitive policies, and conflict resolution strategies. By improving access to quality education in rural Kashmir, it is possible to create a more equitable educational environment and ensure that all students, regardless of their socioeconomic background, have the opportunity to succeed.